The Impact of Digital Transformation on Corporate Tax Avoidance: Evidence from China - Kun Xie; Wei Huang (Discrete Dynamics in Nature and Society, 2023)
Digital transformation plays an important role in reshaping the core competitiveness of enterprises and achieving high-quality development. Based on panel data of Chinese A-share listed companies in Shanghai and Shenzhen from 2009 to 2019, this study examines the impact of digital transformation on corporate internals from the perspective of corporate tax avoidance. It finds that digital transformation significantly inhibits corporate tax avoidance by improving the quality of corporate internal controls; its inhibitory effect on corporate tax avoidance shows significant heterogeneity when firms are in different tax collection intensities and receive different amounts of government subsidies; and the inhibition of corporate tax avoidance significantly improves the efficiency of corporate investment. The research in this study expands the theoretical understanding of digital transformation and corporate tax avoidance and provides relevant insights for the government to promote the deep integration of the digital economy with the real economy.